Adenovirus Encoding Tumor Necrosis Factor Alpha and Interleukin 2 Induces a Tertiary Lymphoid Structure Signature in Immune Checkpoint Inhibitor Refractory Head and Neck Cancer - Clubb, James H. A.; Kudling, Tatiana V.; Heiniö, Camilla; Basnet, Saru; Pakola, Santeri; Cervera Carrascón, Víctor; Santos, João Manuel; Quixabeira, Dafne C. A.; Havunen, Riikka; Sorsa, Suvi; Zheng, Vincent; Salo, Tuula; et al. (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors (ICI) have provided significant improvement in clinical outcomes for some patients with solid tumours. However, for patients with head and neck cancer, the response rate to ICI monotherapy remains low, leading to the exploration of combinatorial treatment strategies. In this preclinical study, we suggest combining ICI with an oncolytic adenoviruses encoding TNFa and IL-2 to achieve superior tumour growth control and improved survival outcomes. The in vitro effect of Ad5/3-E2F-D24-hTNFa-IRES-hIL2 was characterized through analyses of virus replication, transgene expression and lytic activity using head and neck cancer patient derived cell lines. Mouse models of ICI naïve and refractory oral cavity squamous cell carcinoma were established to evaluate the local and systemic anti-tumour immune response upon ICI treatment with or without adenovirus derived TNFa and IL-2. We delineated the mechanism of action by measuring the metabolic activity and effector function of CD3+ tumour infiltrating lymphocytes (TIL) and transcriptomic profile of the CD45+ tumour immune compartment. Ad5/3-E2F-D24-hTNFa-IRES-hIL2 demonstrated robust replicative capability in vitro across all head and neck cell lines screened through potent lytic activity, E1a and transgene expression. In vivo, in both ICI naïve and refractory models, we observed improvement to tumour growth control and long-term survival when combining anti-PD-1 or anti-PD-L1 with adenovirus encoding TNFa and IL-2 compared to monotherapies. This synergistic effect was verified by striking CD3+ TIL derived granzyme b and interferon gamma production complemented by increased T cell bioenergetics. Notably, interrogation of the tumour immune transcriptome revealed the upregulation of a gene signature distinctive of tertiary lymphoid structure formation upon treatment of ICI refractory tumours with addition of virus to anti-PD-L1 refractory tumours. In addition, we detected an increase in anti-tumour antibody production and expansion of the memory T cell compartment in the secondary lymphoid organs. In summary, adenovirus encoding TNFa and IL-2 potentiates ICI therapy, demonstrated by improved tumour growth control and survival in head and neck tumour-bearing mice. Moreover, the data reveals a potential approach for inducing tertiary lymphoid structure formation. Altogether our results support the clinical potential of combining this adenovirotherapy with anti-PD-1 or anti-PD-L1.